ANTINOCICEPTIVE, ANTI-INFLAMMATORY AND ANTIPYRETIC ACTIVITIES OF THE LEAF METHANOL EXTRACT OF RUTA GRAVEOLENS L. (RUTACEAE) IN MICE AND RATS - Loonat, Firdows; Amabeoku, George Jimboyeka (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: Ruta graveolens has been used to treat toothache, earache, rheumatism and fever with little scientific evidence corroborating these uses.Materials and Methods: The leaf methanol extract of Ruta graveolens was evaluated for antinociceptive activity using the acetic acid writhing and hot-plate tests in mice, also anti-inflammatory and antipyretic activities using the carrageenan-induced oedema and E. coli-induced pyrexia tests in rats, respectively.Results: R. graveolens (100 mg/kg, i.p.), significantly reduced the number of acetic acid-induced writhes by 54 %. R. graveolens (400 mg/kg, i.p.), significantly delayed the reaction time in mice to thermal stimulation 15, 30, 45, and 60 min after treatment. Combined treatment of the lowest and sub-effective doses of the leaf methanol extract (25 mg/kg, i.p.), and indomethacin (10 mg/kg, i.p.) significantly reduced the number of acetic acid-induced writhes in mice. The leaf methanol extract of R. graveolens (50 - 400 mg/kg, i.p.), significantly reduced carrageenan- induced oedema over the 4 h period of testing. Combined treatment of the lowest doses of R. graveolens (25 mg/kg, i.p.) and indomethacin (2 mg/kg, i.p.) produced a significant reduction in carrageenan-induced oedema over the 4 h period of testing. R. graveolens (100 - 400 mg/kg, i.p.) significantly reduced E. coli-induced pyrexia over the 5 h period of testing. Given together, the lowest dose of R. graveolens (25 mg/kg, i.p.) and pentoxifylline (10 mg/kg, i.p.) produced a significant reduction in pyrexia induced by E. coli (50 μg/kg, i.m.) over the 5 h period of measurement. The LD50 value obtained for R. graveolens was greater than 4000mg/kg (p.o), suggesting that the plant species may be safe in or nontoxic to mice. Conclusion: The data obtained indicate that R. graveolens has antinociceptive, anti-inflammatory and antipyretic activities, justifying the use of the plant species by traditional medicine practitioners in the management and treatment of pain, inflammation and fever.